THE INFLUENCE OF SOCIAL INFLUENCE, IMPORT BRAND, TRUST, AND PRICE ON PURCHASE INTEREST IN THRIFT SHOPS ON E-COMMERCE PLATFORMS - Isna Apriliza Aisyah; Adnan; M.Subhan; Khairina AR (RADJA PUBLIKA, 2024)
This research aims to determine and analyse the influence of social influence, import brand, trust, and price on purchase interest in thrift shops on e-commerce platforms. This quantitative study has 96 respondents taken using a probability sampling technique and obtained the data through questionnaires and secondary data from journals and internet sources. The data analysis techniques used are multiple linear regression analysis, classical assumption testing, instrument testing (validity and reliability), hypothesis testing, and the coefficient of determination using the SPSS version 26.0 program. The results of partial tests reveal that social influence, import brand, trust, and price positively and significantly affect purchase interest in thrift shops on e-commerce platforms. Price is the dominant variable influencing purchase interest in thrift shops on e-commerce platforms. The Adjusted R Square value of 0.536 indicates that the dependent variable can be explained by the independent variables (social influence, import brand, trust, and price) by 53.6%, and the remaining 46.4% can be explained by other variables not examined in this study.